Pengaruh Illegal fishing Terhadap Keberlanjutan Sumber Daya Ikan: Kajian Hukum Internasional dan Implementasinya di Tingkat Nasional - Ekananda, Gita Aprilia (Universitas Widya Gama Malang, 2025)
This research explores the impacts and challenges of illegal fishing in Indonesian waters by focusing on aspects of fish resource sustainability, international legal regulations, and strategies and efforts undertaken by the Indonesian government. Geographically, Indonesia has a vast ocean area with abundant potential marine wealth. However, the sustainability of fish resources is faced with serious challenges due to illegal fishing practices by foreign fishermen that harm the marine ecosystem and the country's economy. This practice is not only limited to fishing without a license, but also includes the use of environmentally destructive fishing gear and violations of fisheries boundaries. This research discusses the international and national legal context with a normative legal approach by examining legal materials, both written and unwritten, to obtain conclusions about applicable legal arrangements including UNCLOS 1982, FAO Compliance Agreement 1993, and other agreements governing the prevention of illegal fishing. Law implementation at the national level and law enforcement still face obstacles, such as overlapping regulations and lack of effectiveness of law enforcement officers. The Indonesian government has taken a number of steps to deal with illegal fishing, including strengthening the legal framework, law enforcement, use of technology such as Vessel Monitoring System, and international cooperation. However, challenges persist, and a comprehensive strategy that engages communities to strengthen nationalism values and increase involvement in the country's defense and security is needed